A synergistic herbal formulation targeting Malassezia furfur and Staphylococcus epidermidis for effective dandruff management - Singh, Satyendra Pratap; Kumar, Bhanu; Misra, Ankita; Rawat, Poonam; Tripathi, Deepali; Srivastava, Sharad (Frontiers in Microbiology, 2025)
Dandruff is a chronic scalp condition and the mildest form of seborrheic dermatitis, associated with microbial dysbiosis primarily involving Malassezia furfur and Staphylococcus epidermidis. Conventional anti-dandruff treatments are often limited by recurrence and reliance on synthetic antifungal agents. This study aimed to develop and evaluate a synergistic, oil-based herbal formulation with antimicrobial activity against dandruff-causing microorganisms. The herbal constituent, Eucalyptus citriodora (EC) oil, individually signifies its efficacy against key dandruff-causing microbes, while Centella asiatica and Wedelia trilobata were included for their complementary bioactive and skin-healing properties. A total of three formulations (F1, F2, and F3), containing 8, 10, and 12% EC oil, respectively, were tested for antimicrobial efficacy. The optimized formulations (F2 and F3) exhibited significant antimicrobial activity, resulting in 1.8–1.9-fold and 2.0–2.5-fold reductions in M. furfur and S. epidermidis cell viability, respectively. Fluorescence-based LIVE/DEAD viability assays and scanning electron microscopy (SEM) confirmed membrane disruption and structural damage in the treated cells of M. furfur. In addition, molecular docking and dynamics simulations demonstrated strong binding affinities of Eucalyptus citriodora oil constituents toward lanosterol 14α-demethylase (LDM), suggesting disruption of the ergosterol biosynthesis pathway as a plausible antifungal mechanism. The obtained findings indicated that the formulated herbal combination exerts a multi-targeted antimicrobial effect and represents a promising natural alternative for controlling microbial populations involved in dandruff pathogenesis.